Spatial Cognition and Range Use in Free-Range Laying Hens - Campbell, Dana L. M. (Animals (Basel), 2018)
SIMPLE SUMMARY: Individual free-range laying hens vary in their use of the outdoor range. The outdoor environment is typically more complex and variable than indoor housing and thus range use may be related to differences in spatial abilities. Individual adult hens that never went outside were slower to learn a T-maze task—which requires birds to repeatedly find a food reward in one arm of the maze, compared to outdoor-preferring hens. Pullets that were faster to learn the maze also showed more visits to the range in their first month of range access but only in one of two tested groups. Early enrichment improved learning of the maze but only when the birds were tested before onset of lay. Fear may play a role in inhibiting bird’s spatial learning and their range use. More studies of different enriched rearing treatments and their impacts on fear and learning would be needed to confirm these findings. Overall, these results contribute to our understanding of why some birds choose to never access the outdoor range area. ABSTRACT: Radio-frequency identification tracking shows individual free-range laying hens vary in range use, with some never going outdoors. The range is typically more environmentally complex, requiring navigation to return to the indoor resources. Outdoor-preferring hens may have improved spatial abilities compared to indoor-preferring hens. Experiment 1 tested 32 adult ISA Brown hens in a T-maze learning task that showed exclusively-indoor birds were slowest to reach the learning success criterion (p < 0.05). Experiment 2 tested 117 pullets from enriched or non-enriched early rearing treatments (1 pen replicate per treatment) in the same maze at 15–16 or 17–18 weeks. Enriched birds reached learning success criterion faster at 15–16 weeks (p < 0.05) but not at 17–18 weeks (p > 0.05), the age that coincided with the onset of lay. Enriched birds that were faster to learn the maze task showed more range visits in the first 4 weeks of range access. Enriched and non-enriched birds showed no differences in telencephalon or hippocampal volume (p > 0.05). Fear may reduce spatial abilities but further testing with more pen replicates per early rearing treatments would improve our understanding of the relationship between spatial cognitive abilities and range use.